A three-dimensional analysis method for determining void distribution in asphalt mixture

The method of constructing physical models of asphalt mixture void structures using PVDF water gel and steel pins addresses the limitations of existing evaluation methods, offering a more precise and comprehensive assessment of asphalt mixture performance, enhancing drainage and durability.

CN118533715BActive Publication Date: 2025-03-21GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410607903.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-03-21
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

Current methods for analyzing and evaluating the void structure of asphalt mixtures are limited by their high cost, lack of precision, and inability to accurately reconstruct and visualize the void structure, leading to inadequate evaluation of asphalt road performance, particularly in terms of drainage, load-bearing capacity, and durability.

Method used

A method involving the creation of physical models of asphalt mixture void structures through a series of steps including preparation, fixation, and testing of specimens, followed by comprehensive evaluation using parameters like connectedness, distribution, and geometric features, utilizing PVDF water gel as a consolidating agent and steel pins for structural integrity, allowing for a more accurate and detailed assessment.

Benefits of technology

This approach provides a more intuitive and comprehensive evaluation of asphalt mixture void structures, enabling better understanding and improvement of their performance characteristics, such as drainage and load-bearing capacity, and extending the lifespan of asphalt roads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118533715B_ABST
    Figure CN118533715B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for three-dimensional analysis and determination of void distribution of asphalt mixture, the main steps of which include: preparing asphalt mixture grouting specimens and performing grouting treatment on them; performing internal void structure fixing treatment on the formed characterization specimens; performing analysis and testing on the void structure characterization model specimens of the stripped asphalt mixture to obtain relevant test data; determining and evaluating the connectivity characteristics, distribution characteristics and void geometry characteristics in the void structure system of the asphalt mixture. The method for three-dimensional analysis and determination of void distribution of asphalt mixture involved in the present invention can restore the internal void structure of the asphalt mixture in full scale, and then realize the quantitative analysis of the void structure distribution and characteristics of the asphalt binder asphalt mixture. This method will provide a scientific basis for improving the accuracy of quantitative analysis and evaluation of the void structure distribution and characteristics of asphalt mixtures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road asphalt structure analysis, and in particular to a method for constructing and evaluating the void structure of asphalt mixture using a solid model. Background Art

[0002] Asphalt pavement has many tiny void structures due to the distribution characteristics of aggregate and asphalt. The performance of asphalt pavement is closely related to the distribution of void structure of asphalt mixture. The void structure will affect the density of asphalt pavement and reflect the bearing capacity and compressive resistance of the pavement. The void structure will also affect the drainage performance of asphalt pavement. A good void structure helps to improve the drainage performance of asphalt pavement and reduce the possibility of water accumulation on the road surface, thereby reducing water damage problems and extending the life of asphalt pavement. In addition, the void structure will also affect the properties of asphalt pavement such as skid resistance and crack resistance.

[0003] These studies on asphalt pavement can promote the development and application of asphalt pavement materials and improve the safety, comfort and reliability of roads. In the past few decades, the research on the void structure of asphalt mixtures has focused on topics such as drainage and water damage of asphalt mixtures. In the past, the research mainly constructed and characterized the void structure of asphalt mixtures by CT scanning the entire asphalt mixture specimen. However, there are still some defects in the past research methods. First, the past experimental methods are relatively simple and the experimental costs are relatively high. Secondly, the CT scanning method cannot accurately restore the void structure of asphalt mixtures with high precision, nor can it intuitively reconstruct the void structure of asphalt mixtures. The void structure can only be characterized by modeling and reconstruction, and the accuracy of the characterization parameters is poor. The evaluation method is relatively simple and cannot fully evaluate the void structure of asphalt mixtures. Therefore, it is still urgent to propose a reasonable and effective research method for the characterization of the void structure of asphalt mixtures and a corresponding evaluation method to improve the practicality, economy and accuracy of the characterization of the void structure of asphalt mixtures. Summary of the invention

[0004] The purpose of the present invention is to provide a method for characterizing the void structure of asphalt mixture and an evaluation method, by constructing a physical model of the void structure of asphalt mixture and characterizing the void structure thereby, and proposing a new evaluation method based on the construction method of the present invention. Compared with the traditional evaluation method, the advantage of this evaluation method is that it can display the void distribution model of asphalt mixture in a more intuitive way, and present it in a three-dimensional and visual way; at the same time, on the basis of the traditional evaluation method, it also adds a more comprehensive evaluation system, proposes a new evaluation method, and takes into account the influencing factors of various indicators, which can accurately and comprehensively study and improve the road performance of asphalt mixtures through the void structure of asphalt mixtures. Provide relevant basis. The specific scheme is as follows:

[0005] A method for three-dimensional analysis and determination of void distribution in asphalt mixture comprises the following steps:

[0006] S1. Prepare asphalt mixture grouting test specimens and grouting gelling liquid, and perform grouting treatment on the asphalt mixture specimens;

[0007] S2. Curing the grouting asphalt mixture specimens, and fixing the internal void structure system model after the curing is completed;

[0008] S3. Stripping the external asphalt mixture of the void structure system model that has been cured and solidified, testing the obtained void model and obtaining relevant test data;

[0009] S4. Calculate and determine the basic evaluation index parameter values ​​of the asphalt mixture void distribution model;

[0010] S5. Based on the basic evaluation parameter values, a comprehensive evaluation of voids is conducted to evaluate the connectivity characteristics, distribution characteristics, and void geometry characteristics of the asphalt mixture void distribution.

[0011] The research method involved in this invention is mainly based on the distribution of void structure of asphalt mixture and its evaluation to carry out systematic research. V A unified quantitative analysis of various performance indicators of the void structure of asphalt mixtures can be achieved with high accuracy. The distribution of the void structure of asphalt mixtures and various performance indicators can be evaluated and determined through the quantitative results. This will propose a new research and quantitative evaluation method for the study of the void structure of asphalt mixtures, and provide relevant basis for the influence of the void structure on the actual road performance of asphalt mixtures.

[0012] The asphalt mixture grouting specimen involved in the present invention comprises one specimen and three groups of parallel tests, and the grouting gelling liquid material is PVDF hydrogel; the asphalt mixture grouting specimen mold size information is specifically as follows: the mold is a cylindrical steel mold with an inner diameter of 152.5 mm and a height of 127 mm.

[0013] The asphalt mixture grouting specimen involved in the present invention is prepared by a rotary compaction method, with specific reference to "Test Procedure for Asphalt and Asphalt Mixture in Highway Engineering" T0736-2011: the asphalt binder adopts the currently commonly used road asphalt, namely 70# asphalt, 90# asphalt, SBS modified asphalt, rubber powder modified asphalt and high-viscosity and high-elastic asphalt; the asphalt mixture gradation selects the commonly used road asphalt mixture gradation type, namely AC, OGFC and SMA; the aggregate adopts the commonly used aggregate in road engineering, and the filler adopts limestone powder, fly ash, silica fume or cement.

[0014] The invention relates to the preparation of asphalt mixture grouting specimens, wherein the isolating agent is a mixture of talcum powder and glycerol, a mixed solution of sodium alkyl sulfonate and sodium fatty alcohol ether sulfate, and the isolation between the asphalt mixture specimen and the mold can be achieved.

[0015] The grouting gelling liquid involved in the present invention is specifically a PVDF hydrogel grouting liquid, and the PVDF is dissolved in a solvent and then mixed with a crosslinking agent and an initiator in a predetermined ratio to prepare the grouting gelling liquid. The specific preparation process is: PVDF, an acrylic acid crosslinking agent, and an ammonium sulfate initiator are placed in a stirring tank in a predetermined ratio to fully mix the three, and then heated after mixing to perform grouting of the test piece.

[0016] In the preparation of PVDF hydrogel, dimethylformamide is selected as the solvent, and the solute mass fraction is 20%; an acrylate crosslinker is selected as the crosslinker, and the dosage is 10% of the total volume of the solution; and an ammonium sulfate initiator is selected as the initiator, and the dosage is 0.5% of the total mass of the solution.

[0017] The present invention relates to grouting treatment of asphalt mixture specimens, and the specific process is as follows: the asphalt mixture specimen is placed in a grouting mold, sealed and inspected for sealing; the grouting liquid is mixed evenly in a stirring pot and added to a grouting pump, the grouting rate is set to 30ml / min-50ml / min, and the grouting pressure is set to 703kg / m 2 After the grouting is completed, the pressurized state is maintained for 10-15 minutes. After the grouting is completed, the surface of the specimen is ensured to be moist. If the gaps on the surface of the specimen are not completely filled with the grouting liquid, the grouting process should be repeated until a 0.5mm liquid film is observed on the surface of the specimen; after the grouting is completed, open the pressurized mold and wipe the liquid overflowing from the surface of the asphalt mixture.

[0018] The asphalt mixture specimens were grouting treated with a KEN screw grouting pump as the grouting equipment. The bottom grouting mold and the asphalt mixture specimen were customized in a 1:1 ratio to ensure the sealing of the grouting process.

[0019] The present invention relates to fixing the internal void structure system model, and the specific scheme for fixing the steel bar penetration of the asphalt mixture specimen is as follows: the vertical direction of the specimen: the circular holes with a diameter of 6 mm are preset at the top and bottom of the mold to arrange the vertical steel bar insertion range, with the center position of the top and bottom molds as the layout center, and circular steel bar positioning holes with a diameter of 6 mm are radially arranged around, and the interval between adjacent positioning holes and the distance from the top or bottom edge are 13.5 mm; the horizontal direction of the specimen: the horizontal steel bar penetration position is determined by the vertical penetration position. There are a total of 112 circular steel bar positioning holes in the vertical direction, and the steel bar insertion position is the center position of the preset circular steel bar positioning hole, and the error range does not exceed the preset circle area range.

[0020] The invention relates to fixing an internal void structure system model. The steel chisel and equipment information used to fix the internal void structure system model are as follows: the diameter of the vertical fixing steel chisel is 3 mm and the length is 130 mm, the diameter of the horizontal fixing steel chisel is 3 mm and the length is 155 mm, and the material used for the steel chisel is manganese alloy steel. The equipment used for fixing the steel chisel is a WEW-1000 microcomputer hydraulic universal testing machine. The resistance of the steel chisel in the process of penetrating the asphalt mixture test piece will be monitored in real time to ensure that the internal void structure will not be damaged during the penetration process.

[0021] The invention relates to fixing the internal void structure system model, and the steps of fixing the internal void structure system model with a steel chisel are specifically as follows: before pressure penetration, the steel chisel is fixed at the center of a circular steel chisel positioning hole on an asphalt mixture specimen mold, and the steel chisel is vertically downward to ensure that the asphalt mixture specimen can be smoothly penetrated when pressurized;

[0022] The pressure penetration sequence of the steel drill is from the center of the outer circle circular steel drill positioning hole to the inner circle, with a pressing speed of 0.5cm / min and a pressing depth of 63.5mm. If the pressure value of the sensor in the instrument panel increases suddenly after pressurization, stop pressurizing, record the position of the pressed circular hole, measure the penetration depth, cut off the unpenetrated steel drill, and add the drill according to the corresponding positioning hole at the bottom. The penetration depth is the length of the cut steel drill. Repeat the pressure penetration process until the steel drill fills more than 90% of the positioning holes at the top of the specimen. The same operation is performed for the horizontal steel drill penetration. After the penetration is completed, the void characterization model can be fixed. If longitudinal penetration is not possible, horizontal penetration is used for fixation and reinforcement.

[0023] The present invention involves stripping the external asphalt mixture of a void structure system model that has been cured and solidified. The specific steps of the external asphalt mixture are: placing a grouted asphalt mixture specimen fixed with a steel bar in an oven at a temperature of 150°C-180°C for 6h-12h, and then transferring the specimen to a vibration device for vibration stripping of the asphalt mixture, vibrating until the asphalt mixture is basically peeled off, and finally using a steel bar to manually peel off the asphalt mixture that has not fallen off, so as to obtain the void structure system model.

[0024] The present invention involves testing the obtained void model and obtaining relevant test data. Before the test, the void structure system model needs to be laser cut. The equipment and cutting method are as follows: the equipment used is an IPG fiber laser cutting machine. The cutting method for the three-dimensional model is: select a row of steel chisels passing through the center of the circle on the upper surface of the specimen as the axis, and then use the axis and the row of steel chisels parallel to the axis as the cutting standard line. The cutting is centered on the standard line, and the cutting position is 6.75mm on both sides of the center line. According to this rule, 11 longitudinal sections can be cut and cut from the cutting position closest to the edge of the specimen to the middle of the specimen. After each section is cut, the relevant index data is measured immediately as the original data for calculating the void distribution evaluation.

[0025] The present invention involves testing the obtained gap model and obtaining relevant test data, and the test method and indicators are specifically as follows:

[0026] Determination of the total volume of the voids: For the uncut three-dimensional void model, immerse the three-dimensional void model in a graduated cylindrical barrel so that the model is submerged below the liquid surface, and record the volume of the water level change in the container. This volume is recorded as V1, where V1 is the sum of the total volume of the model voids and the volume of the inserted fixed steel bar. Test the steel bar volume V2 again, and the total volume of the model voids V=V1-V2.

[0027] Determination and calculation of connected void ratio: 11 longitudinal sections were taken to analyze the void distribution of the void three-dimensional model. The void structure that penetrates from the top to the bottom of the model is defined as a connected void, the void structure that does not connect the top and bottom is defined as a semi-connected void, and the void closed inside is defined as a closed void. The number of connected voids, semi-connected voids and closed voids in the void three-dimensional model was counted, and the connected void ratio of each section was calculated. The calculation formula is:

[0028]

[0029] Among them, n si is the total number of connected channels in the i-th section, i = 1, 2, 3, ..., 11; N is the total number of gaps, including the sum of connected gaps, semi-connected gaps and closed gaps.

[0030] Determination and calculation of the average area of ​​the void cross section: The area of ​​the void structure of each model interface is measured by an approximate calculation method, and then the void structure areas of n test sections are summed to obtain the total void structure area S0. The average of S0 according to the number of sections n can be obtained to obtain the average area S of the void cross section. The calculation formula of the average area S of the void cross section is as follows:

[0031]

[0032] Among them, S0 is the total void structure area of ​​each section, n is the number of void structure sections, and n is 11.

[0033] Determination and calculation of the equivalent diameter of the void area: The equivalent diameter of the void area is the total void structure area S of different cross sections. i The equivalent diameter is the diameter of a circle with the same area. The equivalent diameter d of the gap area in each cross section i The calculation formula is:

[0034]

[0035] Among them, S i is the total void structure area of ​​each cross section, i = 1, 2, 3, ..., 11.

[0036] The present invention relates to a comprehensive evaluation of voids, characterized in that, in step S5, the comprehensive evaluation of voids is performed, and the absolute values ​​of the total void volume and the average area of ​​a single void cross-section are used as indicators for intuitively evaluating the void size at various locations in the test piece, and directly comparing the sizes can compare the void richness of the asphalt mixture; the connected void ratio and the void equivalent diameter are evaluated, and the coefficient of variation of the connected void ratio and the void equivalent diameter test data is calculated, and the distribution characteristics of the connected void ratio test data can be obtained through the coefficient of variation; wherein the coefficient of variation can reflect the degree of discreteness of the void equivalent diameter, a small degree of discreteness indicates that the void sizes at various locations in the test piece are similar, and a large degree of discreteness indicates that the void sizes at various locations in the test piece are greatly different.

[0037] The evaluation of the total void volume is characterized by referring to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"

[0038] T0736-2011: The void ratio is less than 6% for dense graded asphalt mixture, with less total void volume. Based on the test model, the dimensions are: diameter 152.5mm, height 127mm, and the void volume is 175cm 3 The following are specimens with less voids; the asphalt mixture with a void ratio of 6% to 10% is a semi-open-graded asphalt mixture. Similarly, based on the test model, the void volume is 290cm 3 The following are specimens with larger voids; those with a void ratio greater than 10% are asphalt crushed stones, which belong to open-graded asphalt mixtures, i.e., the void volume is greater than 290cm 3 This is a large gap specimen.

[0039] The characteristic of evaluating the test data of the connected porosity and the void equivalent diameter is that the coefficient of variation of the connected porosity test data is set as B v-l The coefficient of variation of the gap equivalent diameter test data is B v-k , the calculation formula of the coefficient of variation is unique, and the calculation satisfies:

[0040] Calculate the standard deviation δ of the test data, and the calculation formula is:

[0041]

[0042] Where δ is the standard deviation of the test data, and the δ calculation method refers to B v-l and B v-k The standard deviation calculation method in the calculation process; n is the sample size, and the specific number of cross sections is 11, that is, n = 11; x i is the test data of the corresponding indicators of each section. When calculating the coefficient of variation of the connected void ratio, x i Replace with When calculating the equivalent diameter of the gap, x i Replace with d i , where i = 1, 2, 3, …, n; μ is the average value of the test data.

[0043] The coefficient of variation calculation formula for the test data is:

[0044]

[0045] Among them B v is the coefficient of variation of the test data, which can be replaced by the coefficient of variation of the connected void ratio test data B v-l And the coefficient of variation B of the gap equivalent diameter test data v-k ; δ is the standard deviation of the test data; μ is the mean value of the test data.

[0046] The coefficient of variation B of the connected porosity test data v-l The evaluation shows that the coefficient of variation reflects the degree of data dispersion, and the connected void ratio reflects the proportion of connected voids in the cross section. The coefficient of variation value range can be used to know the degree of dispersion and analyze the void characteristics of the specimen. v-k The evaluation shows that the coefficient of variation reflects the degree of data dispersion, and the void equivalent diameter reflects the degree of void size in the cross section. A small degree of dispersion indicates that the void sizes in the specimen are similar, and a large degree of dispersion indicates that the void sizes in the specimen are very different. The coefficient of variation value range can be used to know its dispersion and analyze the void characteristics of the specimen. The coefficient of variation range is divided and evaluated as follows, with B v Represents the coefficient of variation of the two indicators:

[0047] (1) When the coefficient of variation B v When the absolute value is in the interval [0,0.1], it means that the data fluctuates less, has a lower degree of discreteness, and is relatively stable. The connected void ratio index shows that the connected voids are evenly distributed in the specimen. The void equivalent diameter index shows that the voids in the specimen are similar in size, and the voids of different sizes are evenly distributed in the specimen.

[0048] (2) When the coefficient of variation B v When the absolute value is in the interval (0.1, 0.3], the fluctuation of the data is at a medium level and has a certain degree of discreteness. The connected void ratio index shows that the connected voids show a cluster distribution feature in the specimen, and the void morphology of clustered connected voids appears in the specimen. The void equivalent diameter index shows that there is a certain degree of difference in the size of the voids in various parts of the specimen, and the large and small voids show a cluster distribution feature in the specimen, and the void morphology of clustered large voids or clustered small voids appears in the specimen.

[0049] (3) When the coefficient of variation B v When the absolute value is in the interval (0.3,1), it means that the data fluctuates greatly, has a high degree of discreteness, and is relatively unstable. The connected void ratio index shows that the connected voids are randomly distributed in the specimen. The void equivalent diameter index shows that the void sizes vary greatly in the specimen, and the distribution of voids of different sizes is randomly distributed. The void morphology of densely distributed or no void distribution appears in the specimen. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is the asphalt mixture specimen mold diagram.

[0051] Description of main component symbols:

[0052] 1. Asphalt mixture specimen mold guide plate; 2. Asphalt mixture specimen mold top cover reserved hole; 3. Asphalt mixture specimen mold. DETAILED DESCRIPTION

[0053] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present examples are conventional reagents, methods and equipment in the art.

[0054] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0055] A method for three-dimensional analysis and determination of void distribution in asphalt mixture, comprising:

[0056] S1. Prepare asphalt mixture grouting test specimens and grouting gelling liquid, and perform grouting treatment on the asphalt mixture specimens;

[0057] S2. Curing the grouting asphalt mixture specimens, and fixing the internal void structure system model after the curing is completed;

[0058] S3. Stripping the external asphalt mixture of the void structure system model that has been cured and solidified, testing the obtained void model and obtaining relevant test data;

[0059] S4. Calculate and determine the basic evaluation index parameter values ​​of the asphalt mixture void distribution model;

[0060] S5. Based on the basic evaluation parameter values, a comprehensive evaluation of voids is conducted to evaluate the connectivity characteristics, distribution characteristics, and void geometry characteristics of the asphalt mixture void distribution.

[0061] The method for three-dimensional analysis and determination of void distribution in asphalt mixture proposed in this embodiment is adopted, and the specific steps are as follows:

[0062] S1: Asphalt mixture grouting specimens include test group 1 and test group 2, each group contains three test specimens; the grouting gelling liquid material is PVDF hydrogel; the asphalt mixture specimens of test group 1 use the same type of asphalt binder, and use different types of gradations for comparative analysis of void distribution; the asphalt mixture specimens of test group 2 use the same type of gradation, and use different types of asphalt for comparative evaluation of void distribution. The specific size information of the asphalt mixture grouting specimen mold is as follows: the mold is a cylindrical steel mold with an inner diameter of 152.5mm and a height of 127mm.

[0063] The mold selected for preparing asphalt mixture grouting specimens, the asphalt mixture specimen mold 3 should have heat insulation properties, be made of nickel-chromium alloy steel, be cylindrical in shape, and have dimensions of 127mm in depth, 4mm in inner diameter, and 177.8mm in outer diameter; the asphalt mixture is made to have a thickness of 127mm and a diameter of 152.4mm. The internal void structure system model is fixed. The specific steel drill fixing scheme for the asphalt mixture specimen is as follows: formulate the guide plate 1 of the asphalt mixture specimen mold. The size information of the guide plate 1 is: a nickel-chromium alloy steel disc with a diameter of 152.4mm. The vertical direction of the guide plate injection plan: a reserved hole 2 with a diameter of 6mm is preset on the top cover of the circular asphalt mixture specimen mold. The vertical steel drill insertion range is arranged on the top and bottom of the mold. The center position of the top cover 2 of the asphalt mixture specimen mold is the layout center, and circular steel drill positioning holes with a diameter of 6mm are arranged radially around the top and bottom molds. The interval between adjacent positioning holes and the distance from the top or bottom edge are 13.5mm; the horizontal direction of the specimen: the horizontal steel drill penetration position is determined by the vertical penetration position. There are a total of 112 circular steel drill positioning holes in the vertical direction. The steel drill insertion position is the center position of the preset circular steel drill positioning hole, and the error range does not exceed the preset circle area.

[0064] The asphalt of the present invention uses SBS modified asphalt, the performance index of the asphalt refers to JTGE202011 "Test Procedure for Asphalt and Asphalt Mixture in Highway Engineering", the grading uses OGFC-13, and the filler uses limestone powder as the filler.

[0065] The asphalt mixture grouting specimens are prepared by the rotary compaction method, with specific reference to the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" T0736-2011: Preparation of Asphalt Mixture Grouting Specimens. The isolation agent is specifically a mixture of talcum powder and glycerol, or a mixed solution of sodium alkyl sulfonate and sodium fatty alcohol ether sulfate, to achieve isolation between the asphalt mixture specimen and the mold.

[0066] The grouting gelling liquid is specifically a PVDF hydrogel grouting liquid, which is prepared by dissolving PVDF in a solvent and then mixing a crosslinking agent and an initiator in a predetermined ratio. The specific preparation process is: PVDF, an acrylic crosslinking agent, and an ammonium sulfate initiator are placed in a stirring tank in a predetermined ratio to fully mix the three, and then heated after mixing to perform grouting of the specimen.

[0067] In the preparation of the PVDF hydrogel described in step S1, dimethylformamide is selected as the solvent, and the mass fraction of the solute is prepared to be 20%; an acrylate crosslinker is selected as the crosslinker, and the dosage is 10% of the total volume of the solution; and an ammonium sulfate initiator is selected as the initiator, and the dosage is 0.5% of the total mass of the solution.

[0068] The asphalt mixture specimens were grouted. The specific process was as follows: the asphalt mixture specimens were placed in the grouting mold, sealed and inspected for tightness; the grouting liquid was mixed evenly in the mixing pot and added to the grouting pump. The grouting rate was set to 40ml / min and the grouting pressure was set to 703kg / m 2 After the grouting is completed, the pressurized state is maintained for 10 minutes. After the grouting is completed, the surface of the specimen is ensured to be moist. If the gaps on the surface of the specimen are not completely filled with the grouting liquid, the grouting process should be repeated until a 0.5mm liquid film is observed on the surface of the specimen; after the grouting is completed, open the pressurized mold and wipe the liquid overflowing from the surface of the asphalt mixture.

[0069] The asphalt mixture specimens were grouting treated with a KEN screw grouting pump as the grouting equipment. The bottom grouting mold and the asphalt mixture specimen were customized in a 1:1 ratio to ensure the sealing of the grouting process.

[0070] S2: Maintain the grouted asphalt mixture specimens. The specific process of maintaining the grouted asphalt mixture specimens is as follows: put the grouted asphalt mixture specimens into a constant temperature oven at 80°C for 6 hours. The high temperature induces the cross-linking reaction of the hydrogel. After the maintenance is completed, the hydrogel material forms strength and solidifies.

[0071] The internal void structure system model is fixed. The void structure system model fixing process and key points are as follows: after the maintenance is completed, the asphalt mixture specimen is placed in a pressurized pile injection instrument, and the steel bar is inserted by pressurizing both sides in turn. The steel bar is nailed into the circular steel bar positioning hole with a preset diameter of 6 mm to fix the semi-connected void structure and the closed void structure in the specimen.

[0072] The internal void structure system model is fixed. The steel chisel and equipment information used to fix the internal void structure system model are as follows: the vertical fixed steel chisel has a diameter of 3mm and a length of 130mm, the horizontal fixed steel chisel has a diameter of 3mm and a length of 155mm, and the steel chisel is made of manganese alloy steel. The equipment used for fixing the steel chisel is a WEW-1000 microcomputer hydraulic universal testing machine. The resistance of the steel chisel during the penetration of the asphalt mixture specimen will be monitored in real time to ensure that the penetration process will not damage the internal void structure.

[0073] The internal void structure system model is fixed. The specific steps of fixing the internal void structure system model with a steel chisel are as follows: before pressure penetration, the steel chisel is fixed to the center of the circular steel chisel positioning hole on the asphalt mixture specimen mold, and the steel chisel is pointed vertically downward to ensure that it can smoothly penetrate the asphalt mixture specimen when pressurized.

[0074] The pressure penetration sequence of the steel drill is from the center of the circular steel drill positioning hole in the outer circle to the inner circle, with a pressing speed of 0.5cm / min and a pressing depth of 63.5mm. If the pressure value of the sensor in the instrument panel increases suddenly after pressurization, stop pressurizing, record the position of the pressed circular hole, measure the penetration depth, cut off the uninserted steel drill, and add the drill according to the corresponding positioning hole at the bottom. The penetration depth is the length of the cut steel drill. Repeat the pressure penetration process until the steel drill fills more than 90% of the positioning holes at the top of the specimen. The same operation is performed for the horizontal steel drill penetration. If the longitudinal penetration is not possible, the horizontal penetration is used for fixing and reinforcement. The horizontal steel drill penetration position is the circular hole position where the pressure value increases suddenly during the longitudinal steel drill penetration. After the penetration is completed, the fixation of the void characterization model can be completed.

[0075] There are three types of voids: connected voids, semi-connected voids and closed voids.

[0076] S3: For the void structure system model that has been cured and solidified, the external asphalt mixture is stripped. The specific steps of the external asphalt mixture are as follows: the grouted asphalt mixture specimen fixed with a steel bar is placed in an oven at a temperature of 160°C for 10 hours, and then the specimen is transferred to a vibration device for vibration stripping of the asphalt mixture until the asphalt mixture is basically peeled off. Finally, the asphalt mixture that has not fallen off is manually peeled off with a steel bar to obtain the void structure system model.

[0077] The obtained void model was tested and relevant test data was obtained. Before the test, the void structure system model needed to be laser cut. The equipment and cutting method were as follows: The equipment used was an IPG fiber laser cutting machine. The cutting method for the three-dimensional model was as follows: a row of steel chisels passing through the center of the upper surface of the specimen was selected as the axis, and then the axis and the row of steel chisels parallel to the axis were used as the cutting standard line. The cutting was centered on the standard line, and the cutting position was 6.75 mm on both sides of the center line. According to this rule, 11 longitudinal sections can be cut and cut from the cutting position closest to the edge of the specimen to the middle of the specimen. After each section was cut, the relevant index data was measured immediately as the original data for calculating the void distribution evaluation.

[0078] The obtained void model is tested and relevant test data is obtained. The specific test methods and indicators are as follows:

[0079] (1) Determination of connected void ratio: 11 cross sections were taken to observe the void morphology of the three-dimensional model. The void structure that runs through the upper surface of the model to the lower surface is defined as the connected void. The total number of voids in the model was observed and counted. The connected void ratio follows the calculation formula: n si is the total number of connected channels in the i-th section, i = 1, 2, 3, ..., 11; N is the total number of voids in the i-th section, including the sum of connected voids, semi-connected voids and closed voids.

[0080] The connected void ratio of the void characterization model was measured, and the average value of the test was taken three times to obtain the connected void ratio of each section of the model as shown in Table 1.

[0081] (2) Determination of the total void volume: After the entire characterization model is constructed, immerse the model in a graduated water-filled measuring cylinder so that the entire model is submerged below the water surface, and calculate the volume of the water level change, which is recorded as V1. V1 includes the characterization model, that is, the total void volume of the entire specimen, as well as the volume of the inserted fixed steel bar and the volume of the support. This part of the volume can be obtained by testing in the same way, and this part of the volume is recorded as V2. That is, the total void volume V = V1-V2.

[0082] The total void volume of the void characterization model was measured and tested three times, and the average value was taken to obtain the total void volume of the model as shown in Table 1.

[0083] (3) Determination of the average area of ​​the void cross section: The area of ​​the void structure of each model interface is measured by an approximate calculation method, and then the void structure areas of the 11 test cross sections are summed to obtain the total void structure area S0. The average void cross section area S is obtained by taking the average value of S0 according to the number of cross sections n. The calculation formula for the average void cross section area S is: Where n is the number of void sections in the cross section participating in the void area calculation, that is, n is 11.

[0084] The average area of ​​the void cross section of the void characterization model was measured. The average area of ​​the void cross section obtained by testing 11 cross sections is shown in Table 1, model test data table.

[0085] (4) Determination of the equivalent diameter of the gap: Measure the total area A of the gaps on 11 sections, in mm 2 , the calculation formula of the gap equivalent diameter d is: Where S i is the total void area on each cross section.

[0086] The void characterization model was used to measure the void equivalent diameter, and 11 sections were tested to obtain the average area of ​​the void equivalent diameter of each section. See Table 1 for the model test data.

[0087] Table 1. Model test data table

[0088]

[0089] S5: Comprehensively evaluate the gaps. The specific evaluation method is as follows:

[0090] The coefficient of variation of the connected porosity test data is calculated as B v-l The coefficient of variation of the gap equivalent diameter test data is B v-k , the calculation satisfies: /

[0091] Calculate the standard deviation δ of the test data, and the calculation formula is:

[0092]

[0093] Where δ is the standard deviation of the test data; the δ calculation method refers to B v-l and B v-k The standard deviation calculation method in the calculation process; n is the sample size, and the specific number of cross sections is 11, that is, n = 11; x i is the test data of the corresponding indicators of each section; μ is the average value of the test data of the corresponding indicators.

[0094] From the data in Table 1, it can be calculated that the standard deviation of the connected porosity test data is 5.381, and the standard deviation of the void equivalent diameter test data is 1.162.

[0095] Calculate the coefficient of variation of the test data, where the coefficient of variation calculation satisfies:

[0096]

[0097] Among them B vis the coefficient of variation of the test data, which can be replaced by the coefficient of variation of the connected void ratio test data B v-l And the coefficient of variation B of the gap equivalent diameter test data v-k ; δ is the standard deviation of the corresponding index test data; μ is the mean value of the corresponding index test data.

[0098] From the data in Table 1, the coefficient of variation B of the gap equivalent diameter test data can be calculated. v-l =25.96%, analysis coefficient of variation B v-l The coefficient of variation B of the connected porosity test data can be obtained by analysis: v-l The absolute value is in the interval (0.1, 0.3], and the fluctuation of the data is at a medium level with a certain degree of discreteness. This shows that the connected voids have the characteristics of cluster distribution in the specimens, and the void morphology of clustered connected voids appears in the specimens.

[0099] Calculate the coefficient of variation B of the gap equivalent diameter test data v-k =4.39%, analysis coefficient of variation B v-k Available, B v-k It is in the interval [0,0.1], which means that the data fluctuation of the void equivalent diameter is small, indicating that the void sizes are similar in the specimens and the void sizes are evenly distributed in the specimens.

[0100] In summary, through calculation, it can be obtained that the void ratio of the specimen is 13.6%. The total volume of the voids in the specimen can be used to judge that the specimen is a large void specimen. Further analysis of the connected void ratio shows that the connected voids of the specimen show a distribution characteristic of settlement distribution, indicating that the drainage performance of the specimen will be different in various parts of the specimen. Analysis of the void equivalent diameter of the specimen shows that the void size of the specimen shows a uniform distribution characteristic, indicating that the voids in various parts of the specimen are of similar size and the difference between large and small voids is not large.

[0101] The method for three-dimensional analysis and determination of asphalt mixture void distribution involved in the present invention has relevant reference and basis for evaluating and analyzing the void structure of different asphalt mixture specimens. It is applied to the research and analysis of the void connectivity performance of actual asphalt mixture specimens, and the quantitative analysis of the void structure of the asphalt mixture specimens is realized based on the index analysis. The analysis results are highly accurate, and the void structure characteristics of the asphalt mixture specimens can be evaluated and determined through the quantitative results, which will provide relevant basis for improving the void connectivity performance of the asphalt mixture specimens.

[0102] As described above, the three-dimensional analysis and determination method and evaluation method of the asphalt mixture void distribution provided by the present invention are introduced in detail. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; any simple modifications, changes and equivalent structural changes made to the above embodiments based on the technical essence of the invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for three-dimensional analysis and determination of void distribution in asphalt mixture, characterized in that: The determination method mainly includes the following steps: S1. Prepare asphalt mixture grouting test specimens and grouting gelling liquid, and perform grouting treatment on the asphalt mixture specimens; S2. Curing the grouting asphalt mixture specimens, and fixing the internal void structure system model after the curing is completed; S3. Stripping the external asphalt mixture of the void structure system model that has been cured and solidified, testing the obtained void model and obtaining relevant test data; S4. Calculate and determine the basic evaluation index parameter values ​​of the asphalt mixture void distribution model; S5. Based on the basic evaluation parameter values, conduct a comprehensive evaluation of voids to evaluate the connectivity characteristics, distribution characteristics, and void geometry characteristics of asphalt mixture voids; The internal void structure system model is fixed according to step S2, specifically: After the curing is completed, the asphalt mixture specimen is placed in a pressurized pile injection instrument, and the steel bar is inserted by pressurizing both sides successively. The steel bar is nailed into the circular steel bar positioning hole with a preset diameter of 6 mm to fix the semi-connected void structure and the closed void structure in the specimen; the specific steel bar fixing scheme for the asphalt mixture specimen is as follows: Vertical direction of the specimen: The circular holes with a diameter of 6 mm are preset at the top and bottom of the mold to arrange the vertical steel bar insertion range. The center of the top and bottom molds is used as the layout center, and circular steel bar positioning holes with a diameter of 6 mm are radially arranged around. The interval between adjacent positioning holes and the distance from the top or bottom edge are 13.5 mm; Horizontal direction of the specimen: The horizontal steel bar penetration position is determined by the longitudinal penetration position; There are a total of 112 circular steel bar positioning holes in the longitudinal direction, and the steel bar insertion position is the center of the preset circular steel bar positioning hole, and the error range does not exceed the preset circle area. The resistance during the penetration of the steel bar into the asphalt mixture specimen will be monitored in real time to ensure that the internal void structure will not be destroyed during the penetration process; the steps of using the steel bar to fix the internal void structure system model are as follows: before pressure penetration, the steel bar is fixed to the center of the circular steel bar positioning hole on the asphalt mixture specimen mold, and the steel bar is vertically downward to ensure that the asphalt mixture specimen can be smoothly penetrated during pressurization; the pressure penetration sequence of the steel bar is from the center of the outer circle circular steel bar positioning hole to the inner circle, and the pressing speed is 0.5cm / min, and the pressing depth is set to 63.5mm; after pressurization, if the sensor pressure value in the instrument panel increases suddenly, stop pressurizing, record the position of the pressed circular hole, measure the penetration depth, and Cut off the uninserted part of the steel drill, and add additional drills according to the corresponding positioning holes at the bottom. The penetration depth is the length of the cut steel drill; repeat the pressure penetration process until the steel drill fills more than 90% of the positioning holes at the top of the test piece; perform the same operation for the transverse steel drill penetration. If the longitudinal penetration is not possible, use transverse penetration for fixation and reinforcement. The transverse steel drill penetration position is determined as follows: when the pressure value of the test machine increases sharply during the longitudinal steel drill penetration process, record the current longitudinal steel drill penetration depth, and record the position of the reserved circular hole of the mold where the current longitudinal steel drill starts to penetrate from the top. The penetration position is at the recorded depth position, and the penetration direction is the same depth through the circular hole to the center of the test piece. After the penetration is completed, the fixation of the void characterization model can be completed; In step S4, the basic evaluation index parameter values ​​of the asphalt mixture void distribution model are calculated and determined, and the test method and index are specifically as follows: Determination of the total volume of voids: For the uncut three-dimensional void model, immerse the three-dimensional void model in a cylindrical barrel with scales, submerge the model below the liquid surface, and record the volume of the water level change in the container, which is recorded as V1. V1 is the sum of the total volume of the model void and the volume of the inserted fixed steel bar; the steel bar volume V2 is tested again, and the total volume of the model void V = V1-V2; Determination and calculation of connected void ratio: 11 longitudinal sections were taken to analyze the void distribution of the void three-dimensional model. The void structure that penetrates from the top surface to the bottom of the model is defined as a connected void, the void that does not connect the top and bottom surfaces is defined as a semi-connected void, and the void closed inside is defined as a closed void. The number of connected voids, semi-connected voids and closed voids in the void three-dimensional model was counted, and the connected void ratio of each section was The calculation formula is: Among them, n si is the total number of connected channels in the i-th section, i = 1, 2, 3, ..., 11; N is the total number of voids in the i-th section, including the total number of connected voids, semi-connected voids and closed voids; Determination and calculation of the average area of ​​the void cross section: The area of ​​the void structure of each model interface is measured by an approximate calculation method, and then the void structure areas of n test cross sections are summed to obtain the total void structure area S0. The average void cross section area S can be obtained by taking the average value of S0 according to the number of cross sections n. The calculation formula for the average void cross section area S is as follows: Among them, S0 is the total area of ​​the void structures in each cross section, n is the number of void structures in the cross section, and the value of n is 11; Determination and calculation of the equivalent diameter of the void area: The equivalent diameter of the void area is the total void structure area S of different cross sections. i The equivalent diameter is the diameter of a circle with the same area. The equivalent diameter d of the gap area in each cross section i The calculation formula is: Among them, S i is the total void structure area of ​​each cross section, i = 1, 2, 3, ..., 11.

2. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: The asphalt mixture grouting specimens described in step S1 include 3 parallel test specimens; the grouting gelling liquid material is PVDF hydrogel; the asphalt mixture grouting specimen mold size information is specifically: the mold is a cylindrical steel mold with an inner diameter of 152.5 mm and a height of 127 mm; The asphalt mixture grouting specimens described in step S1 are prepared by rotary compaction method, with specific reference to "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" T0736-2019: the asphalt binder adopts the commonly used road asphalt, i.e. 70# asphalt, 90# asphalt, SBS modified asphalt, rubber powder modified asphalt and high viscosity and high elastic asphalt; the asphalt mixture gradation selects the commonly used road asphalt mixture gradation type, i.e. AC, OGFC and SMA; the aggregate adopts the commonly used aggregate in road engineering, and the filler adopts limestone powder, fly ash, silica fume or cement; In the preparation of the asphalt mixture grouting specimen described in step S1, the isolation agent is specifically a mixture of talcum powder and glycerol, a mixed solution of sodium alkyl sulfonate and sodium fatty alcohol ether sulfate, so as to achieve isolation between the asphalt mixture specimen and the mold.

3. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: The grouting gelling liquid described in step S1 is specifically PVDF hydrogel grouting liquid, and PVDF is dissolved in a solvent and then mixed with a crosslinking agent and an initiator in a predetermined ratio to prepare the grouting gelling liquid; the specific preparation process is: PVDF, an acrylic acid crosslinking agent, and an ammonium sulfate initiator are placed in a stirring tank in a predetermined ratio to fully mix the three, and then heated to grout the specimen after mixing; In the preparation of the PVDF hydrogel described in step S1, dimethylformamide is selected as the solvent, and the mass fraction of the solute is prepared to be 20%; an acrylate crosslinker is selected as the crosslinker, and the dosage is 10% of the total volume of the solution; and an ammonium sulfate initiator is selected as the initiator, and the dosage is 0.5% of the total mass of the solution.

4. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: The asphalt mixture specimen is grouted as described in step S1. The specific process is as follows: the asphalt mixture specimen is placed in a grouting mold, sealed and inspected for tightness; the grouting liquid is mixed evenly in a stirring pot and added to a grouting pump. The grouting rate is set to 30ml / min-50ml / min, and the grouting pressure is set to 703kg / m 2 After the grouting is completed, the pressurized state is maintained for 10-15 minutes; after the grouting is completed, the surface of the specimen is ensured to be moist. If the gaps on the surface of the specimen are not completely filled with the grouting liquid, the grouting process should be repeated until a 0.5 mm liquid film can be observed on the surface of the specimen; after the grouting is completed, the pressurized mold is opened to wipe the liquid overflowing from the surface of the asphalt mixture; The asphalt mixture specimen is grouted in step S1, and the grouting equipment used is a KEN screw grouting pump. The bottom grouting mold and the asphalt mixture specimen are customized in a 1:1 scale to ensure the sealing of the grouting process.

5. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: The step S2 is to perform curing on the grouted asphalt mixture specimens. The specific process of curing the grouted asphalt mixture specimens is as follows: the grouted asphalt mixture specimens are placed in a constant temperature oven at 80°C for 4-8 hours. The high temperature induces a cross-linking reaction of the hydrogel. After the curing is completed, the hydrogel material forms strength and solidifies. The internal void structure system model is fixed as described in step S2. The steel bar and equipment information used to fix the internal void structure system model are as follows: the diameter of the vertically fixed steel bar is 3 mm and the length is 130 mm, the diameter of the horizontally fixed steel bar is 3 mm and the length is 155 mm, and the material used for the steel bar is manganese alloy steel; the equipment used for fixing the steel bar is a WEW-1000 microcomputer hydraulic universal testing machine, and the resistance of the steel bar during the penetration of the asphalt mixture specimen will be monitored in real time to ensure that the internal void structure will not be damaged during the penetration process.

6. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: The step S3 is to perform external asphalt mixture stripping on the void structure system model that has been cured and solidified. The specific steps of the external asphalt mixture stripping are as follows: put the grouted asphalt mixture specimen fixed with a steel bar into an oven at a temperature of 150°C-180°C for 6h-12h, and then transfer the specimen to a vibration device for asphalt mixture vibration stripping, vibrate until the asphalt mixture is basically peeled off, and finally use a steel bar to manually peel off the asphalt mixture that has not fallen off, so as to obtain the void structure system model; The obtained void model is tested and relevant test data is obtained as described in step S3. Before the test, the void structure system model needs to be laser cut. The equipment and cutting method are as follows: the equipment used is an IPG fiber laser cutting machine; the cutting method for the three-dimensional model is: a row of steel chisels passing through the center of the upper surface of the specimen is selected as the axis, and then the axis and the row of steel chisels parallel to the axis are used as the cutting standard line. The cutting is centered on the standard line, and the cutting position is 6.75 mm on both sides of the center line. According to this rule, 11 longitudinal sections can be cut and cut in order from the cutting position closest to the edge of the specimen to the middle of the specimen. After each section is cut, the relevant index data is measured immediately as the original data for calculating the void distribution evaluation.

7. The method for three-dimensional analysis and determination of void distribution in asphalt mixture according to claim 1, characterized in that: Step S5 is to comprehensively evaluate the voids. The absolute values ​​of the total void volume and the average void cross-sectional area are used as indicators for intuitively evaluating the void size of each part of the test piece. Direct comparison of the sizes can compare the void richness of the asphalt mixture. The connected void ratio and the void equivalent diameter are evaluated, and the coefficient of variation of the connected void ratio and the void equivalent diameter test data is calculated. The distribution characteristics of the connected void ratio test data can be obtained through the coefficient of variation. The coefficient of variation can reflect the degree of dispersion of the equivalent diameter of the voids. A small dispersion degree indicates that the void sizes in the specimen are similar, while a large dispersion degree indicates that the void sizes in the specimen are very different. The characteristic of evaluating the test data of the connected porosity and the void equivalent diameter is that the coefficient of variation of the connected porosity test data is set as B v-l The coefficient of variation of the gap equivalent diameter test data is B v-k , the calculation formula of the coefficient of variation is unique, and the calculation satisfies: Calculate the standard deviation δ of the test data, and the calculation formula is: Where δ is the standard deviation of the test data, and the δ calculation method refers to B v-l and B v-k The standard deviation calculation method in the calculation process; n is the sample size, and the specific number of cross sections is 11, that is, n = 11; x i is the test data of the corresponding indicators of each section. When calculating the coefficient of variation of the connected void ratio, x i Replace with When calculating the equivalent diameter of the gap, x i Replace with d i , where i = 1, 2, 3, ..., n; μ is the average value of the test data; The coefficient of variation calculation formula for the test data is: Among them B v is the coefficient of variation of the test data, which can be replaced by the coefficient of variation of the connected void ratio test data B v-l And the coefficient of variation B of the gap equivalent diameter test data v-k ;δ is the standard deviation of the test data;μ is the mean value of the test data; The coefficient of variation B of the connected porosity test data v-l The evaluation shows that the coefficient of variation reflects the degree of data dispersion, and the connected void ratio reflects the proportion of connected voids in the cross section. The coefficient of variation value range can be used to know its dispersion and analyze the void characteristics of the specimen. Coefficient of variation B of the gap equivalent diameter test data v-k The evaluation shows that the coefficient of variation reflects the degree of data dispersion, and the void equivalent diameter reflects the degree of void size in the cross section. A small degree of dispersion indicates that the void sizes in the specimen are similar, and a large degree of dispersion indicates that the void sizes in the specimen are very different. The coefficient of variation value range can be used to know the degree of dispersion and analyze the void characteristics of the specimen. The coefficient of variation range is divided and evaluated as follows, with B v Represents the coefficient of variation of the two indicators: (1) When the coefficient of variation B v When the absolute value is in the interval [0,0.1], it means that the data fluctuates less, has a lower degree of discreteness, and is relatively stable. The connected void ratio index indicates that the connected voids are evenly distributed in the specimen. The void equivalent diameter index indicates that the voids in various locations of the specimen are similar in size, and the voids of different sizes are evenly distributed in the specimen. (2) When the coefficient of variation B v When the absolute value is in the interval (0.1, 0.3], the fluctuation of the data is at a medium level and has a certain degree of discreteness; the connected void ratio index shows that the connected voids have a cluster distribution feature in the specimen, and the void morphology of clustered connected voids appears in the specimen; the void equivalent diameter index shows that the void sizes in different parts of the specimen have a certain degree of difference, and the large and small voids have a cluster distribution feature in the specimen, and the void morphology of clustered large voids or clustered small voids appears in the specimen; (3) When the coefficient of variation B v When the absolute value is in the interval (0.3,1), it means that the data fluctuates greatly, has a high degree of discreteness, and is relatively unstable; the connected void ratio index shows that the connected voids are randomly distributed in the specimen; the void equivalent diameter index shows that the void sizes in various parts of the specimen vary greatly, and the distribution of voids of different sizes is randomly distributed, and the void morphology with dense distribution or no void distribution appears in the specimen.